LEARNING STRATEGY IMPLEMENTATION (APPLICATION) OF INDEPENDENT VALUE LEARNING DURING COVID-19 - Aminah Aminah (JURNAL SOCIUS, 2022)
This study aims to examine how implementation learning strategies (application of learning the value of independence develop and what factors influence, both those that support or hinder learning activities during the Covid-19 pandemic at the State Integrated PAUD institution Pembina Timur Banjarmasin, which is located at Jalan Pangeran Hidayatullah (Lingkar). In the North) Gang SMP 14 RW. 001 RT. 05 NO. 47 Benua Anyar Village, East Banjarmasin District. The study used a qualitative descriptive approach with multi-site research. The results found in the field that the strategy for developing the value of independence for early childhood is to establish cooperation good relationship between the school and parents, providing daily, weekly and monthly activities with holistic programs. The resulting independence of children is being able to be separated from their parents, being responsible for their duties, choosing play activities, putting bags in lockers, removing and installing shoes That is, wearing their own clothes, tidying up play equipment and writing utensils, washing hands, eating and drinking alone, brushing teeth, wearing mukena and other prayer utensils. Dare to appear in front of the class and the camera when studying online.